A socio-technical case study on integrating product management and devops practices in governmental software delivery - Oliveira, Bruna Pinos de (2026)
Dissertação (mestrado) — Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Ciência da Computação, Programa de Pós-Graduação em Informática, 2026.